INCREASING THE EFFECTIVENESS OF WEBGIS-BASED VILLAGE IRRIGATION NETWORK MANAGEMENT IN GAMPONG KEUTAPANG KEC. NISAM, DISTRICT NORTH ACEH - Zara Yunizar; Muthmainnah; Nura Usrina; Mukhlis; Zainal, Zalfie Ardian; Tjut Adek, Rizal; Maizuar (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2025)
Keutapang Village is located in Nisam District, North Aceh Regency, Aceh Province with a village area of 123.4 ha. This village has 120 ha of agricultural land and rice as the main commodity, but the productivity of the planting season and harvest cannot be maximized due to the lack of irrigation that has been built, thus it is necessary to increase the effectiveness of irrigation management by mapping irrigation as information for village irrigation development planning. The rural irrigation map contains information on the location, situation and condition of irrigation, and the priority scale for improving the WEBGIS-based network. The purpose of this community service activity was to produce a village irrigation network map and educate village officials in increasing the effectiveness of irrigation network management through WEBGIS-based mapping. The mapping stages included measurement surveys using GPS, digitizing the surface of the area through Google Earth, depicting the layout with the AutoCAD application and making maps with QGIS/ArcGIS software. This community service activity in Keutapang Village, Nisam District produced informative and attractive village irrigation geospatial maps. The result of this activity is a digital irrigation map whose printout is submitted to the village officials. It is hoped that this map can be published and used as a basis for future sustainable village development planning.